The Westminster handbook to women in American religious history - Lindley, Susan Hill, 1945-2005.; Stebner, Eleanor J., 1960- (Louisville, Ky. : Westminster John Knox Press, 2008)
The Westminster Handbook to Women in American Religious History provides an affordable and accessible reference to over 750 outstanding individual women and women's organizations in American religious history.--From publisher description.
Includes bibliographical references.
Keywords: Women and religion -- United States -- Encyclopedias; United States -- Religion -- Encyclopedias; Encyclopedias